Study on High Thermal Conductivity of X-ray Anode with Composite Diamond Substrate. (August 2019) - Li, Xinwei; Zhang, Pingwei; Li, Ye; Wang, Xin
Abstract: The thermal loading capacity of the anode of a micro-focus X-ray source is an important factor to limit the output power. In this paper, a composite reflective anode model with a thick film diamond layer as the target substrate of X-ray source was proposed. With the advantage of high thermal conductivity of the diamond film, the heat accumulated in a micro-focus area can be quickly output, to improve the thermal loading capacity of the anode. A composite anode with diamond substrate was modeled and simulated with the finite element analysis method. By studying the principle of high thermal conductivity of composite anode in the numerical simulation and comparing the composite anode with copper substrate anode, the essential causes of the high thermal conductivity of the anode with diamond substrate were identified. The relevant technical parameters were obtained in the simulation and comparison, which can be used for the design of anode of micro-focus X-ray sources.